Mass mortality of unknown etiology in alpine newts (Ichtyosaura alperstris veluchiensis) in an alpine lake in Greece - AZMANIS, PN; SCHMIDT, V; SAINIS, I; MARSCHANG, RE; PAPAIOANNOU, H (Journal of the Hellenic Veterinary Medical Society, 2021)
A mass mortality in alpine newts (Ichthyosaura alpestris veluchiensis) was observed in May/June 2013, in Drakolimni lake on Smolikas Mountain, Northwest Greece. 1300 alpine newts were found dead in two events. In 1998 a similar incident was recorded in the nearby lake of Timfi Mt. Newts of every stage and sex were affected, presenting incoordination and inability to float evenly. Ten animals were submitted for complete pathological examination. Field environmental measurements (water temperature, oxygen saturation, pH, conductance, nitric/phosphate concentration) and samples (water, snow, benthos) were collected for ecotoxicological and quality analysis. Necropsy, microbiology (parasitology, bacteriology, mycology), histopathology, molecular investigations (Ranavirus spp, Batrachochytridium dendrobatidis, Batrachochytridium salamandrivorans), quality and ecotoxicological examinations did not indicate a causative source for the mortality. To the author´s knowledge this is the biggest mortality of unknown etiology reported in free-living alpine newts in Europe.